2018
DOI: 10.1021/acs.chemrev.8b00008
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Biochemical Perspectives of Protein Lysine Methylation

Abstract: Protein lysine methylation is a distinct posttranslational modification that causes minimal changes in the size and electrostatic status of lysine residues. Lysine methylation plays essential roles in regulating fates and functions of target proteins in an epigenetic manner. As a result, substrates and degrees (free versus mono/di/tri) of protein lysine methylation are orchestrated within cells by balanced activities of protein lysine methyltransferases (PKMTs) and demethylases (KDMs). Their dysregulation is o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
204
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 204 publications
(209 citation statements)
references
References 336 publications
(1,148 reference statements)
4
204
0
1
Order By: Relevance
“…Despite recent success in structural, mechanistic, and inhibition studies on KMTs, the biocatalytic potential of KMTs remains to be established . Enzymatic assays revealed that human KMTs exhibited a high degree of specificity for the methylation of lysine analogues that differed in stereochemistry, side‐chain length, and main chain .…”
Section: Introductionmentioning
confidence: 99%
“…Despite recent success in structural, mechanistic, and inhibition studies on KMTs, the biocatalytic potential of KMTs remains to be established . Enzymatic assays revealed that human KMTs exhibited a high degree of specificity for the methylation of lysine analogues that differed in stereochemistry, side‐chain length, and main chain .…”
Section: Introductionmentioning
confidence: 99%
“…To date, five core histone proteins have been described, namely, H1, H2A, H2B, H3 and H4. Histones are rich in lysine and the accessibility of DNA for transcription is regulated by PTMs in the lysine side chains, generally through an interplay of acetylation and methylation . Thereby, methylation and demethylation is catalysed by respective enzymes.…”
Section: Introductionmentioning
confidence: 94%
“…In addition to our efforts to find selective G9a inhibitors based on the structural modification of ETPs, we aimed to develop a robust strategy to identify new protein substrates and modification sites of PMTs. As we briefly mentioned in Section 1, the existence of over 200 PMTs has been predicted, and many methylation sites have already been reported, but we lack a comprehensive methylome map of PMTs, their substrates, and their methylation sites . Considering that SAM is a common methyl donor in protein methylation reactions, we have focused on SAM analogues as chemical detectors for substrate labeling .…”
Section: Methylation Substrate Detectors: Sam Analoguesmentioning
confidence: 99%
“…Systematic structural characterization, along with bioinformatics studies on PMTs in humans, indicates that the human genome encodes over 200 PMTs, including 50 SET [Su(var)3‐9, Enhancer‐of‐zeste, Trithorax]‐domain‐containing PMTs and 130 seven‐beta‐strand class (7BS) PMTs . In terms of protein substrates, PMTs can be mainly classified into two families depending on the target amino acid residue, i. e., PKMTs (protein lysine methyltransferases) and PRMTs (protein arginine methyltransferases), as shown in Scheme . However, methylome analysis to characterize the substrates and methylation sites of the PMTs remains greatly underdeveloped.…”
Section: Introductionmentioning
confidence: 99%